NEW AESTHETICS OF PORCELAIN PAINTINGS OF THE EIGHT FRIENDS OF ZHUSHAN IN JINGDEZHEN FOR CULTURAL AND CREATIVE PRODUCT DESIGN - Bailu, Li; Panthupakorn, Poradee; Suvimolstien, Chusak (Fine Arts Journal: Srinakharinwirot University, 2024)
This research aims to study the evolution of artistic styles and the factors influencing porcelain paintings of the “Eight Friends of Zhushan”; and to analyze the new styles, techniques and aesthetics of porcelain paintings of the “Eight Friends of Zhushan”. The aesthetics, technology, and drawing methods for porcelain paintings of the Eight Friends of Zhushan were employed for cultural and creative product design. According to the documentary research, fieldwork, and the interviews with involved experts, aesthetical and historical values in porcelain paintings of the 10 members from the Eight Friends of Zhushan (i.e., Wang Qi, Wang Dafan, Xu Zhongnan, Deng Bishan, Wang Yeting, Cheng Yiting, Tian Hexian, Bi Botao, He Xuren, and Liu Yucen) were perceived. The research distinguishes the aesthetic and historical value of ceramic painting and identifies connections between the new aesthetics of the Eight Friends’ ceramic paintings and concepts for designing creative cultural products. Insights gained from expert interviews and surveys informed the creation of five sets of cultural products that incorporate the unique styles of the Eight Friends’ ceramic paintings with contemporary functional design. These products blend diversity, modernity, and multiple techniques to reflect new and contemporary aesthetics. Some items feature controlled light and shadow techniques and can be assembled in various ways, providing a rich and varied aesthetic experience.